Polyherbal Formulation Approach: A Promising Wound Healing Strategy: Pharmaceutical Science-Herbal Technology - Tanimu, Habibu; Vijayan, Nadasha Koonath; Omana Sukumaran, Bindhu (International Journal of Life Science and Pharma Research, 2022)
Wound healing still remains as an unmet therapeutic challenge and a significant clinical and economic burden among medical society even with considerable research on advanced wound care globally. Myriads of wound healing products and strategies are currently available. Some of these products are synthetic chemical moieties like chlorhexidine, betadine etc with systemic side effects such as crystalluria, methaemoglobinaemia, renal impairment, ototoxicity and renal/thyroid dysfunctions. Even the advanced wound healing therapy such as bioengineered cellular wound therapies and stem cells therapies come with some disadvantages such as unaffordability to common man and difficulty in obtaining sufficient stem cells due to their low regenerative potential and ethical issues. The shortcomings associated with current available wound healing strategies necessitated the increasing interest in the use of medicinal plants in wound management. The growing interest towards medicinal plants primarily resulted as an outcome of scientific advancement in delineating the principles and molecular mechanisms behind the contribution of various phytoconstituents in them. Meticulous combination of several medicinal plants in the form of polyherbal formulations (PHFs) such as Ankaferd, herboheal and Ari’s wound healing cream are reported to be safe and provide effective wound healing compared to the use of single plant. Several reviews on wound healing properties of individual plants and PHFs have been reported, but the multitargeted, synergistic and the complementary contributions of individual phytoconstituents in the PHFs at different complex stages of wound healing need to be given the desired attention. The aim of this review is to provide together a comprehensive report on the latent potentials of the positive herb-herb combination as a promising approach to wound healing. Our objective is to systematically collect research, and review articles from various open access research databases and study them to bring out the salient features of PHFs in relation to the effective wound management. A composite drug approach such as PHF is a better treatment option for improved wound management as many phytoconstituents in it can synergistically tackle multiple wound healing processes simultaneously. They are reported to be effective on multidrug resistant bacteria by inhibiting the complex quorum sensing regulated virulence factors’ production and eventually causing their death. Transformations of active phytoconstituents that are reported to occur in PHFs may lead to formation of novel pharmacologically active compound/s, and nanoparticle/s. These transformations may lead to discovery of novel wound healing drug/s that researchers and pharmaceutical industries need to pay more attention to.